Ceramics in Pazyryk tombs of the Mongolian Altai : : Classification, Terminology and Patterns (Studia Archaeologica, 2024)
Presently, within the Mongolian Altai Mountains, specifically within the Bayan-Olgii province, a total of 68 pottery artifacts have been unearthed from 50 graves across 21 burial complexes. Consequently, this article aims to delineate the classification and terminology pertaining to Mongolian Pazyryk culture pottery types based on the aforementioned 68 objects, alongside an examination of patterns. Pazyryk study literature has identified over ten distinct types of pottery, categorized according to discernible features or attributes. Among these, the most prevalent include jugs, vases, crocks, pots, and bowls. However, within the Pazyryk tombs in Mongolia, only three types of pottery—jugs, vases, and crocks—were discovered, leading to their classification into 3 primary types and 5 subtypes. The structural composition of Pazyryk pottery diverges from that of Xiongnu pottery, typically exhibiting a coarser and more rugged texture. Nonetheless, Pazyryk pottery showcases a greater richness and variety of patterns compared to its Xiongnu counterpart. Mongolian Pazyryk pottery designs or patterns are categorized into 3 main forms encompassing 9 types. An examination of Mongolian Pazyryk pottery, as well as the broader Pazyryk culture, suggests a well-developed and refined pottery artistry characterized by diverse and distinctive forms, intricate patterns, decorations, and a distinction between funerary and domestic pottery. It appears that these vessels were crafted and distributed locally by indigenous artisans, albeit with discernible influences from neighboring cultures and even distant regions.Монгол Алтайн пазырык булшны ваар сав: Ангилал, нэр томьёо ба хээ чимэглэлТовчлол. Монгол Алтайд малтан судласан пазырыкийн 21 оршуулгын цолцолборын 50 булшнаас илэрсэн 68 ваарны 34 ваарыг их бага хэмжээгээр сэргээн харах боломжтой гэж үзэн нэгтгэн дүгнэж ангилах оролдлогыг хийв. Монголын пазырыкийн ваар савны ангилал, нэр томьёо, хээ чимэглэлийн асуудал нь ерөнхийдөө ангиллын эргэн тойронд төвлөрсөн бөгөөд ваар савны үйлдэх технологи, он цагийн асуудлыг хөндөлгүй зөвхөн хэрэглээний асуудлыг товч авч үзлээ. Хээ чимэглэлийг 3 хэлбэрийн 9 төрөлд хуваан ангилав.Түлхүүр үг. Төмрийн түрүү үе, Пазырыкийн соёл, пазырыкийн булш, ваар сав, домбо, хотго, бутан, зурмал хээ